Activity of Linezolid in an In Vitro Pharmacokinetic-Pharmacodynamic Model Using Different Dosages and Staphylococcus aureus and Enterococcus faecalis Strains with and without a Hypermutator Phenotype - Ba, Boubakar B. (American Society for Microbiology (ASM), 2010)
The influence of antibiotic dosages and bacterial mutator phenotypes on the emergence of linezolid-resistant mutants was evaluated in an in vitro pharmacokinetic-pharmacodynamic model. A twice-daily 0.5-h infusion of a 200-, 600-, or 800-mg dose for 48 h was simulated against four strains (MIC, 2 μg/ml): Staphylococcus aureus RN4220 and its mutator derivative MutS2, Enterococcus faecalis ATCC 29212, and a mutator clinical strain of E. faecalis, Ef1497. The peak concentrations (4.38 to 4.79, 13.4 to 14.6, and 19.2 to 19.5 μg/ml) and half-lives at β-phase (5.01 to 6.72 h) fit human plasma linezolid pharmacokinetics. Due to its bacteriostatic property, the cumulative percentages of the dosing interval during which the drug concentration exceeded the MIC (T > MIC), 66.6 and 69.1% of the dosing interval, were not significant, except for Ef1497, with an 800-mg dose and a T > MIC of 80.9%. At the standard 600-mg dosage, resistant mutants (2- to 8-fold MIC increases) were selected only with Ef1497. A lower, 200-mg dosage did not select resistant mutants of E. faecalis ATCC 29212, but a higher, 800-mg dosage against Ef1497 did not prevent their emergence. For the most resistant mutant (MIC, 16 μg/ml), characterization of 23S rRNA genes revealed the substitution A2453G in two of the four operons, which was previously described only in in vitro mutants of archaebacteria. Nevertheless, this mutant did not yield further mutants under 600- or 200-mg treatment. In conclusion, linezolid was consistently efficient against S. aureus strains. The emergence of resistant E. faecalis mutants was probably favored by the rapid decline of linezolid concentrations against a strong mutator, a phenotype less exceptional in E. faecalis than in S. aureus.